2021
DOI: 10.52566/msu-econ.8(1).2021.144-153
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Mathematical Modelling of the Effectiveness of the National System for Combatting Cyber Fraud and Legalisation of Criminal Proceeds Based on Survival Analysis Methods

Abstract: In modern world, the digitalisation of financial relations, the development of innovative technologies, and the emergence and use of cryptocurrencies for payments lead to an increase in the number of cyber frauds in the financial sector and their intellectualisation, increasing the illegal outflow of funds abroad. Ineffective decisions and inaction in counteracting these threats lead to large-scale negative consequences of both financial and social nature. The purpose of this study is to implement economic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…These programs support robust forensic data analytics to identify undesirable behaviors. Such measures aid in curbing financial fraud by helping to investigate fraud, resolve legal and compliance risks within the bank, monitor the illegal behavior of employees, detect theft of critical digital assets, help with risk escalation procedures, develop interfaces for performance improvement, integrate data from social media platforms to gauge potential offender (Ahram et al, 2017;Kuzmenko et al, 2021). A study by (Singh et al, 2022) found that user behavior-based insider threat detection leads to fewer false positives, faster threat detection and significantly higher classifier accuracy.…”
Section: Results Of K-nn Fraud Prioritization and Validationmentioning
confidence: 99%
See 4 more Smart Citations
“…These programs support robust forensic data analytics to identify undesirable behaviors. Such measures aid in curbing financial fraud by helping to investigate fraud, resolve legal and compliance risks within the bank, monitor the illegal behavior of employees, detect theft of critical digital assets, help with risk escalation procedures, develop interfaces for performance improvement, integrate data from social media platforms to gauge potential offender (Ahram et al, 2017;Kuzmenko et al, 2021). A study by (Singh et al, 2022) found that user behavior-based insider threat detection leads to fewer false positives, faster threat detection and significantly higher classifier accuracy.…”
Section: Results Of K-nn Fraud Prioritization and Validationmentioning
confidence: 99%
“…Fraud mapping is vital because it offers several advantages, including the following: monitoring for potentially fraudulent and high-risk events (Thomas et al, 2013), calculating transaction risk factors to determine the legitimacy (Adel et al, 2022) and monitoring fraudulent online activities (Kuzmenko et al, 2021), providing alerts and analysis tools for administrators (Hidayati et al, 2021) and facilitating compliance with privacy and security regulations (Kuzmenko et al, 2021), prevent complex fraud and increase coverage (Antje and Gary, 2019). Several qualitative and quantitative methods have historically been applied to mapping the two streams.…”
Section: Effective Response System For Internal-led Cyber Fraudsmentioning
confidence: 99%
See 3 more Smart Citations